Genetic Population Structure of the Hard Clam Meretrix meretrix Along the Chinese Coastlines Revealed by Microsatellite DNA Markers - Ye, Yingying; Yan, Chengrui; Senanan, Wansuk; Guo, Baoying; Xu, Kaida; Lü, Zhenming (Frontiers in Marine Science, 2020)
The hard clam Meretrix meretrix is ecologically and economically important in the coastal regions of China. We evaluated the genetic diversity and population structure among eight M. meretrix samples from the Yellow Sea (YS) and South China Sea (SCS) using nine microsatellite DNA loci. Both conventional and model-based population genetic analyses suggested significant genetic divergence between YS and SCS regions (pairwise FST values ranging from 0.014 to 0.056). Samples within each region were not genetically different, except for Zhanjiang which clearly differed from other the four SCS samples. Membership coefficients, estimated by STRUCTURE, suggested some genetic admixture of the two genetic clusters in ZJ. Population genetic structure was detected in SCS region. We detected moderate levels of genetic variation in all eight samples (mean A = 16.111 - 22.111, mean Ar = 14.512 - 19.029, mean Ho = 0.736 - 0.843, mean He = 0.823 - 0.868) and two genetic clusters (mean A = 27.167 - 29.833, mean Ae = 8.834 - 9.471, mean Ar = 26.032 - 27.005, mean Ho = 0.824 - 0.839 and mean He = 0.821 - 0.850). Low levels of Ne estimates were detected in M. meretrix populations. None of the genetic populations had signs of recent genetic bottlenecks. Knowledge on genetic variation and population structure of M. meretrix populations along the Chinese coasts will support the aquaculture management and conservation of M. meretrix, and will provide insights for stock selection in selective breeding programs for these species and delineating management units.